The Role of Islamic Religious Education Teachers and Parents in Cultivating Students' Spirituality in The Modern Era - Isrofuzain Isrofuzain; Meti Fatimah (Abjadia : International Journal of Education, 2026)
This study aims to analyse the roles of Islamic Religious Education (PAI) teachers and parents in fostering students' spiritual attitudes at MI Miftahul Huda Bonangrejo, Bonang, Demak, in the digital era. The background of this research stems from the phenomenon of declining religious interest among students and the significant influence of technology and globalisation on the religious behaviour of elementary school-aged children. Employing a qualitative approach with a case study design, this study involved 12 participants, consisting of the school principal, two PAI teachers, and nine parents. Data were collected through in-depth interviews, participant observation, and documentation, and then analysed using the Miles and Huberman interactive model. The results indicate that PAI teachers play strategic roles as educators of religious values, spiritual guides, moral role models, drivers of the school’s religious culture, and mentors of Islamic-based digital literacy. Meanwhile, parents serve as primary educators through exemplary worship practices, habituation of religious activities, warm religious communication, supervision of technology use, and the creation of a religious family atmosphere. The synergy between PAI teachers and parents has been shown to strengthen students’ religious discipline, social morality, and spiritual awareness. This study concludes that collaboration between schools and families is a crucial foundation for developing students’ spirituality amidst the challenges of the digital era. However, this study is limited to a single educational institution within a specific geographic context, so the findings reflect the characteristics of MI Miftahul Huda Bonangrejo, Demak, and may not fully represent other schools with different social and cultural settings.